A DNA-conjugated small molecule catalyst enzyme mimic for site-selective ester hydrolysis. Issue 8 (24th January 2018) - Flanagan, Moira L.; Arguello, A. Emilia; Colman, Drew E.; Kim, Jiyeon; Krejci, Jesse N.; Liu, Shimu; Yao, Yueyu; Zhang, Yu; Gorin, David J.
Abstract : A DNA-imidazole conjugate, designed to mimic enzyme function, site-selectively hydrolyzes a target ester, but not other esters, with >100-fold rate enhancement compared to free imidazole. Abstract : The challenge of site-selectivity must be overcome in many chemical research contexts, including selective functionalization in complex natural products and labeling of one biomolecule in a living system. Synthetic catalysts incorporating molecular recognition domains can mimic naturally-occurring enzymes to direct a chemical reaction to a particular instance of a functional group. We propose that DNA-conjugated small molecule catalysts (DCats), prepared by tethering a small molecule catalyst to a DNA aptamer, are a promising class of reagents for site-selective transformations. Specifically, a DNA-imidazole conjugate able to increase the rate of ester hydrolysis in a target ester by >100-fold compared with equimolar untethered imidazole was developed. Other esters are unaffected. Furthermore, DCat-catalyzed hydrolysis follows enzyme-like kinetics and a stimuli-responsive variant of the DCat enables programmable "turn on" of the desired reaction.